Strategic environmental assessment policy systems model for solid waste management in Malaysia / Dennis Jeyakumar Victor Devaraj - Victor Devaraj, Dennis Jeyakumar (2014)

(untitled)
This study has examined the Strategic Environmental Assessment (SEA) policy framework for integrating environmental requirements in solid waste management (SWM) policies, plans and programmes (PPP) in Malaysia. The key problem the study frames is the lack of environmental policy integration for SWM. Currently, environmental issues are mainly addressed during the environmental impact assessments (EIA) of SWM facilities, which have resulted in environmental pollution, public protest and public litigation.